The Digital Archive for the Study of Pre-Islamic Arabian Inscriptions: an ERC project - Avanzini, Prof. Alessandra; Prioletta, Dr Alessia; Rossi, Dr Irene (Proceedings of the Seminar for Arabian Studies, 2014)
The Digital Archive for the Study of Pre-Isiamic Arabian Inscriptions (DASI) is a five-year ERC project of the University of Pisa, directed by Prof. A. Avanzini. Started in May 2011, the project seeks to collect the whole corpus of pre-Islamic Arabian inscriptions in an open-access archive, with the aim of fostering studies and scientific publications on the epigraphic heritage of Arabia. The paper describes the main activities carried out in the first two years of the project: the IT research on the cataloguing methodologies of the epigraphic material, the digitization of thousands of pre-Islamic Arabian inscriptions, and the setting up of the archive website for the fruition of the catalogued material, which opened in October 2013. The project also encourages the involvement of international partners and promotes interest in pre-Islamic Arabia through a series of related activities and projects, such as the MEDINA digital library and the IMTO archaeological database, which are promoted in the Arabia Antica portal of the University of Pisa.